The Direct Impact of Blockchain Basic Knowledge and Its Indirect Impact Through Moderating Adoption of Technology Utility Knowledge and Perceived Value to Risk Tolerance in Buying Interest of Crypto Assets - Aries, Aries; Diana Sari, Rafica; Yulianti, Ely; Raefani, Galih (Indonesian Journal Entrepreneurship Finance and Business Management, 2025)
Around the world, Blockchain as an innovation technology of computer science field has developed at a rapid pace, with various utilities across many sectors. The perceived value inherent in cryptographic products has also established crypto as a new asset class in the digital world. This phenomenon has driven an increment of public buying interest in crypto products as a new option within their investment portfolios. This research aims to explore more deeply the factors that influence the formation of value perception in cryptographic products and to what extent the public is aware of and can tolerate the risks that arise when they decide to purchase crypto as a digital asset for investment. The main factors we examine are the basic understanding of blockchain technology and knowledge of the adoption of its usefulness as cognitive and affective factors. This research relates to the study of consumer behaviour using the CAC (Cognitive-Affective-Conative) model approach. The respondents used as samples in this research activity are the citizens of Depok City. This research is conducted for academic and learning purposes only, and not for the purpose of influencing or encouraging the public to invest. We are not responsible for any losses, both material and non-material, arising from any investment actions taken by the public who may be influenced after reading the results of this research.